Treatment of olive oil mill wastewater by silica–alginate–fungi biocomposites - Duarte, Kátia R. (2019)
Olive oil mill wastewater (OMW) generates a wide variety of pollutants depending on the production process and other factors such as olive varieties and cultivation system. Efforts to mitigate the impact of these effluents in the environment have been made by developing more efficient treatment systems in terms of removal of chemical oxygen demand (COD), color, organic compounds, and toxicity. This study is the first that reports the potential of a treatment of OMW by biocomposites of silica–alginate–fungi (Pleurotus sajor caju and Trametes versicolor). The treatment by biocomposites can be considered as a three-step process responsible for the removal of the compounds: (1) adsorption of reactants on the monolithic structure and diffusion to the biological active sites, (2) biodegradation by the fungi, and (3) diffusion of the products resulting from the biodegradation. Both treatments tested showed potential capacity to remove organic compounds, color, COD, and toxicity. The T. versicolor biocomposites were the most effective and responsible for the reduction in color (from 38.4 to 44.9 %), COD (from 42.8 to 63.8 %), and total phenolic content (from 85.3 to 88.7 %) after 29 days of treatment. The toxicity reduction on Portuguese OMW was minimal, but the use of composites on the Moroccan OMW caused a 9.5- to 19-fold reduction in toxicity. Furthermore, the biocomposites showed potential for re-utilization for more 29 days of treatment.